Pengaruh Technolgy Acceptance Model terhadap Minat Mahasiswa Menggunakan Quick Response Code Indonesian Standard (QRIS) sebagai Cashless Society - Wirda Seputri; Andri Soemitra; Nur Ahmadi Bi Rahmani (MES Management Journal, 2023)
The purpose of this study was to determine the effect of perceived trust, perceived benefits, perceived ease of use, and perceived risk on interest in using QRIS as a digital payment instrument. This study uses a quantitative approach. Collecting data using a questionnaire with a simple random sampling technique as many as 98 respondents. Perceived trust, perceived benefits, perceived ease of use and perceived risk have a contribution of 71% to interest in using QRIS, the remaining 29% is explained by other variables outside this research model. The results of the t-test concluded that the variables of perceived trust, perceived benefits, perceived ease of use and perceived risk had a positive and significant effect on interest in using QRIS in Febi Uinsu Medan students. Based on the ANOVA test, the F-count obtained is 60.471 which is greater than the F-table (2.47), the results of the hypothesis indicate that the variable perception of trust with a sign value of 0.000, perceived ease of use with a sign value of 0.033, perceived usefulness with a sign value of 0.13, and the perception of the risk of the 0.000 sign partially affects the interest in using QRIS. So it can be concluded that the perception of trust, perceived benefits, perceived ease of use and perceived risk simultaneously influence the interest in using Quick Response Code Indonesian Standard (QRIS) as a digital payment instrument. Keywords: Consumer Perception, Interests, Qris, Digital Payment Instruments.